The sulfur depot in the rhizosphere of a common wetland plant, Juncus effusus, can support long-term dynamics of inorganic sulfur transformations. (October 2017) - Wiessner, Arndt; Kuschk, Peter; Nguyen, Phuong Minh; Müller, Jochen A.
Abstract: The sulfur cycle in the rhizosphere of constructed wetlands is frequently interlaced with transformations of carbon and nitrogen. Knowledge about the manifold sulfur transformations may thus aid in improving treatment performance of constructed wetlands. In this study, two laboratory-scale constructed wetland models (planted fixed bed reactors; PFR1 and PFR2) were used to investigate inorganic sulfur transformations at various total loads of sulfate and organic carbon. Sulfate, sulfide and elemental sulfur were the most abundant sulfur compounds detected, thus providing evidence for the simultaneous occurrence of dissimilatory sulfate reduction and sulfide oxidation. This co-occurrence was likely enabled by oxygen micro-gradients in the root-near environment, i.e. aerobic sulfide and elemental sulfur oxidation took place mostly at the roots while sulfate and elemental sulfur reduction occurred in the pore water under reduced redox conditions. The rhizosphere was found to be first sink, then source for sulfur during the course of the experiment. Immobilization of reduced sulfur was triggered by catabolism of organic matter coupled to dissimilatory sulfate reduction and the subsequent partial oxidation of generated sulfide. Good plant status was critical for sulfur deposition in the systems. Without externally provided sulfate the sulfur depot of the rhizosphere was a prolonged source for sulfur, which was remobilized into the pore water. Oscillations between sulfide and sulfur (PFR1) or sulfide and sulfate (PFR2) suggested a dynamic interplay between plants and various microbial guilds, i.e. dissimilatory sulfate and sulfur reducers on one side and sulfide and sulfur oxidizers on the other. Graphical abstract: Highlights: The rhizosphere of soft rush can be a substantial sink or source of sulfur. Depot sulfur can support vigorous sulfur transformations over a long time frame. Inorganic sulfur concentrations oscillated during transformation of depot sulfur.